Benefits of an integrated European electricity market - Veit Böckers; Justus Haucap; Ulrich Heimeshoff (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
This paper analyses the benefits of further market integration of European wholesale electricity markets. Major gains from trade are sill left unrealized due to (1) uncomplete market coupling of national wholesale markets, (2) isolated national regulation of capacity and reserve mechanisms (CRM) and (3) a lack of harmonization of national support schemes for renewable energies.
Keywords: 330